Spirituality and parenting among women experiencing intimate partner violence - Kaufman, Caroline C. (Journal of family violence, 2021)
While spirituality and parenting have been examined among caregivers experiencing adversity, less research has explored these factors among mother survivors of intimate partner violence (IPV). Given the potentially protective role of spirituality, understanding how parenting is associated with spirituality is important. The current study explored parenting practices, parent-child communication, and spirituality among 175 women caregivers who had experienced recent IPV. Hierarchical linear regression was used to examine associations between maternal age, education, HIV status, and illicit substance use (model 1); child age and gender (model 2); parent-child comfort communicating about sexual practices, IPV, HIV/AIDS, and substance use (model 3); and positive and negative parenting practices (model 4) with spirituality. Findings suggested positive parenting practices, greater comfort talking about IPV, and greater discomfort talking about substance use were associated with higher spirituality. Results highlight the value of parenting and communication strategies among women caregivers experiencing recent adversity.